2011
DOI: 10.1038/ismej.2011.89
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of ocean warming on the prokaryotic community: evidence from the vibrios

Abstract: The long-term effects of ocean warming on prokaryotic communities are unknown because of lack of historical data. We overcame this gap by applying a retrospective molecular analysis to the bacterial community on formalin-fixed samples from the historical Continuous Plankton Recorder archive, which is one of the longest and most geographically extensive collections of marine biological samples in the world. We showed that during the last half century, ubiquitous marine bacteria of the Vibrio genus, including Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
180
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(185 citation statements)
references
References 39 publications
3
180
1
1
Order By: Relevance
“…Indeed, long-term studies have provided evidence of a significant positive relationship between sea surface temperature and Vibrio occurrence (Vezzulli et al 2012). In the NW Mediterranean, Vibrio infection together with temperature might have contributed to mass mortality events of benthic invertebrates (Vezzulli et al 2010).…”
Section: Relationships Between Vibrio and Environmental Factorsmentioning
confidence: 99%
“…Indeed, long-term studies have provided evidence of a significant positive relationship between sea surface temperature and Vibrio occurrence (Vezzulli et al 2012). In the NW Mediterranean, Vibrio infection together with temperature might have contributed to mass mortality events of benthic invertebrates (Vezzulli et al 2010).…”
Section: Relationships Between Vibrio and Environmental Factorsmentioning
confidence: 99%
“…A possible explanation for this is the lack of comparable data, conducted over a large spatial and temporal scale. To fill in this gap, at least in part, a study was recently conducted to analyze long-term relationships between Vibrio occurrence and climatic variables through retrospective molecular analysis of samples collected by the Continuous Plankton Recorder (CPR) survey in the North Sea (17), where, in recent years, an unexpected increase in the number of bather infections associated with vibrios was reported (see above, and 20,21,22,23).…”
Section: Long-term Effects Of Ocean Warming On the Vibrio Community Imentioning
confidence: 99%
“…biology and ecology are described. Figure 1 shows most relevant effects of ocean warming on vibrios and zooplankters that represent important environmental reservoir for these bacteria (16,17). In addition, recently published studies carried out in the southern North Sea are summarized as they provided the first experimental evidence for a positive and significant relationship between SST and Vibrio occurrence over a multidecadal time scale (17).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations recently showed that Vibrio spp. numbers, including potential pathogens, have increased within the plankton-associated bacterial community of the North Sea during the last half century [31].…”
Section: Introductionmentioning
confidence: 99%